Assessing the performance of TRX and DUF148 antigens for detection of prepatent Guinea worm (Dracunculus medinensis) infection in dogs - Hakimi, Hassan; Weerarathne, Pabasara; Saleh, Meriam N.; Rech, Raquel R.; Bongo Nare, Richard Ngandolo; Tchindebet, Philip Ouakou; Metinou, Sidouin K.; van Loben Sels, Jessica M.; Tritten, Lucienne; Verocai, Guilherme G. (Frontiers in Parasitology, 2025)
IntroductionGuinea worm (GW) is a nematode that causes a neglected tropical disease that is targeted for eradication. GW emergence in animals, particularly dogs, has hampered eradication efforts. Currently, there is no method for diagnosing GW infection in animals during the prepatent period. Previous work has identified two immunoreactive antigens, TRXL-1 (TRX) and DUF148.MethodsThis study developed and assessed the performance of an indirect ELISA using these antigens.ResultsUsing serum samples from experimentally exposed dogs, TRX and DUF148 showed reactivity at 9- and 11-weeks post-exposure, respectively. These antigens were further assessed using sera of dogs from GW-endemic villages in Chad (n=47) and shelter dogs from the non-endemic United States (n=492). DUF148 showed better reactivity and sensitivity of 76.6.% in detecting GW infection in prepatent sera compared to TRX. However, DUF148 cross-reacted with a Brugia pahangi experimental infection serum sample and several shelter dog sera. To mitigate this cross-reaction, we produced 3 peptides that spanned different regions of DUF148. Peptide 3 from the C-terminal was more reactive with prepatent sera and had a sensitivity of 83%; however, the specificity was not superior to whole antigen.DiscussionOur findings could facilitate the development of diagnostic methods for early detection of GW infection in dogs in endemic countries.